DOCUMENTATION OF TRADITIONAL DRUG AND MEDICINE PLANTS USED COMMUNITY IN TALANG SELUAI VILLAGE SUB DISTRICT ULU OGAN DISTRICT OGAN KOMERING ULU, SOUTH SUMATERA PROVINCE - Ria Mariani; Atun Qowiyyah; Mimim Rojena (Prodi Farmasi Fakultas Kedokteran Universitas Hang Tuah, 2021)
Plant utilization is an option for medication including plant utilization that carried out by the community of Talang Seluai village. This research hasbeen done in Talang Seluai Village, ulu ogan district, ogan komering ulu area, South Sumatra province, to list medical plant and medical traditional recipes. This research was conducted in october to december 2016.This research was done by descriptive research using a qualitative methodology. The qualitative research was conducted by interview semi structural based on a list of questions. The result showed that the plants of which used medicinally by the village community of Talang seluai, there were 26 species in 18 families, one plant was not detectable, Yakhian, belongs to Leguminosae. Lamiaceae is the most used plant of all. Leaves was the most used and garden was the most collected among them and boiled in the water was the most drug processing used. At Talang Seluai, there were six traditional drug herbs, consist of two internal drugs (diarrhea and rheumatic medicines) and four external drugs (rheumatic, inflammation, wound and skin disorders).